Pengaruh Blended Learning Berbasis Edmodo dan Motivasi Belajar Terhadap Hasil Belajar IPA Biologi dan Retensi Siswa pada Sistem Peredaran Darah Manusia di Kelas VIII SMP Negeri 5 Medan - Daulay, Utami Alam; Syarifuddin, Syarifuddin; Manurung, Binari (Jurnal Pendidikan Biologi, 2016)
The research was aim to know: (1) influence of blended learning basedÂ  edmodo on learning outcome; (2) influence of blended learning basedÂ  edmodo on retention; (3) influence of motivation on learning outcome; (4) influence of motivation on retention; (5) interaction between blended learning based edmodo and motivation on learning outcome; (6) interaction of blended learning based edmodo and motivation on retention in grade VIII at SMP N 5 Medan. The research was quasy experiment. The analyze data technique were using ANAVA two ways with significance 0.05. the result revealed that: (1) there was influence of blended learning based edmodo on learning outcome (F = 86.668; P = 0.000); (2) there was influence of blended learning based edmodo on retention (F = 35.476; P = 0.000); (3) there was influence motivation on learning outcome (F = 37.597; P = 0.000); (4) there was motivation on retention (F = 13.004; P = 0.000); (5) there was interaction of blended learning based edmodo and motivation on learning outcome (F = 4.942; P = 0.003) and (6) there was interaction of blended learning based edmodo and motivation on retention in grade VIII in SMP N 5 Medan (F = 2.946; P = 0.031).